2017
DOI: 10.1016/j.bjhh.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory profile of patients with sickle cell anemia

Abstract: ObjectiveThis study aimed to describe and analyze clinical and laboratory characteristics of patients with sickle cell anemia treated at the Hemominas Foundation, in Divinópolis, Brazil. Furthermore, this study aimed to compare the clinical and laboratory outcomes of the group of patients treated with hydroxyurea with those patients that were not treated with hydroxyurea.MethodsClinical and laboratorial data were obtained by analyzing medical records of patients with sickle cell anemia.ResultsData from the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
4
11
0
4
Order By: Relevance
“…We studied the hematological indices of all subjects, we found that the majority of SCA patients have a lower hemoglobin and hematocrit levels (7.0 -10.4 g / dl and less than 40%, respectively). These results support previous studies conducted in Nigeria and Brazil [23,24,25]. Although maintaining hemoglobin levels in SCA patients is a principle in managing SCA, it has been reported that patients 866 who tend to develop complications like frequent sever crisis and AVN have higher hemoglobin, hematocrit and RBCs levels than others [23].…”
Section: Discussion:-supporting
confidence: 90%
“…We studied the hematological indices of all subjects, we found that the majority of SCA patients have a lower hemoglobin and hematocrit levels (7.0 -10.4 g / dl and less than 40%, respectively). These results support previous studies conducted in Nigeria and Brazil [23,24,25]. Although maintaining hemoglobin levels in SCA patients is a principle in managing SCA, it has been reported that patients 866 who tend to develop complications like frequent sever crisis and AVN have higher hemoglobin, hematocrit and RBCs levels than others [23].…”
Section: Discussion:-supporting
confidence: 90%
“…It is also observed from this study that 80% of the patients with HbSS were either 20 years of age or less. This age range is similar to the findings of [26] in Brazil who also reported a sickle cell prevalent rate consistent with age range of 20 -29 years. Sickle Cell Disease ultimately results in multiple organ failure and pre-mature death occurring mostly in children under five years and adolescents [11].…”
Section: Discussionsupporting
confidence: 90%
“…Although gender does not present Mortality in sickle disease Pompeo CM, Cardoso AIQ, Souza MC, Ferraz MB, Ferreira Júnior MA, Ivo ML a genetic predominance in SCD, female predominance was observed in the population. 29 Likewise, the observed data regarding genotype are also in line with the worldwide literature that shows that HbSS is the most prevalent genotype in Brazil and worldwide and can reach about 70% of all cases of SCD diagnosed. 30,31 Regarding mortality, the data were also similar.…”
Section: Discussionsupporting
confidence: 84%